The impact of magnetic fields on the chemical evolution of the supernova-driven ISM. Issue 4 (29th November 2016) - Pardi, A.; Girichidis, P.; Naab, T.; Walch, S.; Peters, T.; Heitsch, F.; Glover, S. C. O.; Klessen, R. S.; Wünsch, R.; Gatto, A.
Abstract: We present three-dimensional magneto-hydrodynamical simulations of the self-gravitating interstellar medium (ISM) in a periodic (256 pc) 3 box with a mean number density of 0.5 cm −3 . At a fixed supernova rate we investigate the multi-phase ISM structure, H2 molecule formation and density–magnetic field scaling for varying initial magnetic field strengths (0, 6 × 10 −3, 0.3, 3 μG). All magnetic runs saturate at mass-weighted field strengths of ∼1–3 μG but the ISM structure is notably different. With increasing initial field strengths (from 6 × 10 −3 to 3 μG) the simulations develop an ISM with a more homogeneous density and temperature structure, with increasing mass (from 5 to 85 per cent) and volume filling fractions (VFFs; from 4 to 85 per cent) of warm (300 <  T < 8000 K) gas, with decreasing VFFs from ∼35 to ∼12 per cent of hot gas ( T > 10 5  K) and with a decreasing H2 mass fraction (from 70 to < 1 per cent). Meanwhile, the mass fraction of gas in which the magnetic pressure dominates over the thermal pressure increases by a factor of 10, from 0.07 for an initial field of 6 × 10 −3 μG to 0.7 for a 3 μG initial field. In all but the simulations with the highest initial field strength self-gravity promotes the formation of dense gas and H2, but does not change any other trends. We conclude that magnetic fields have a significant impact on the multi-phase, chemical and thermal structure of the ISM and discuss potential implications and limitations of the model.